Influence of Additivation of Bio-Based Lubricants on Sprayability and Solubility for Cryogenic Minimum Quantity Lubrication - Meier, Trixi; Lermer, Michael; Gross, Daniel; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCSM 2022, 2023)
The development of innovative cooling lubrication strategies is significantly driven by the need to machine materials resistant to high temperatures while taking into account both ecological and economic aspects. Cryogenic minimum quantity lubrication (CMQL) represents a compromise satisfying both efficiency and sustainability in the manufacturing process. A minimal amount of oil is added to the cryogenic medium carbon dioxide (CO2) to ensure both cooling and lubrication during tool engagement. In this context, vegetable oils, so-called triglycerides, can be used with respect to the cooling lubrication concept. The aim of this paper is to analyze various bio-based oils with regard to their solubility, spraying and flow behavior and to investigate the influence of additives on the performance. During the lubrication tests, the additives have shown no influence on the lubricating effects. Thus the chemical properties of the base oils primarily influence the properties with regard to solubility and spray behavior. Finally, the collected results were correlated with machining tests showing only a limited correlation with the aforementioned lubrication tests.
Keywords: CMQL; Milling; Liquid carbon dioxide; Bio-based lubricants

Influence of Carbon Dioxide Temperature on Sprayability and Solubility in Cryogenic Minimum Quantity Lubrication with Bio-Based Lubricants - Meier, Trixi; Lermer, Michael; Gross, Daniel; Hanenkamp, Nico (Manufacturing Driving Circular Economy. GCSM 2022, 2023)
Cryogenic minimum quantity lubrication (CMQL) represents a compromise satisfying both efficiency and sustainability in many manufacturing processes. In previous series of experiments a variation of the thermodynamic state of the cryogenic medium taken from riser bottles could be observed. Consequently, the aim of this study was to specifically control the thermodynamic state of the CO2 and, associated with this, the density after removal from the riser bottles. To achieve this objective conventional cooling was implemented for the CO2 after withdrawal from the riser bundle in order to have a constant liquid state of the CO2 during feeding. The density of the cryogenic medium could be raised from ρ = 550 kg/m3 to over 800 kg/m at a mass flow rate of m˙ CO2 = 5 kg/h with the applied cooling method and can also be stabilized regarding the density pulsation. Subsequently, the effects of temperature-controlled CO2 on the sprayability and solubility in CMQL were examined and resulted in increased atomization of the oils and widening of the spray corridor with a greater main spray length and intensity. In addition stable conditions for the CMQL-supply to the manufacturing process were achieved by a lower pulsation of the CO2-oil mixture.
Keywords: CMQL; Liquid carbon dioxide; Bio-based lubricants